The closers - Connelly, Michael author (New York : Warner Books, 2006)
Years after the death of a sixteen-year-old girl is ruled a suicide, detective Harry Bosch receives DNA evidence that reopens the case, which involves an investigation of a white supremacist with close ties to the LAPD.
National College of Business and Arts
Keywords: Teenage girls -- Crimes against -- Fiction; Detective and mystery fiction